Influence of tree canopy on N2 fixation by pasture legumes and soil rhizobial abundance in Mediterranean oak woodlands. - Carranca, C.; Castro, I. V.; Figueiredo, N.; Redondo, R.; Rodrigues, a R. F.; Saraiva, I.; Maricato, R.; Madeira, M. a V. (The Science of the total environment, 2015)
Symbiotic N2 fixation is of primordial significance in sustainable agro-forestry management as it allows reducing the use of mineral N in the production of mixed stands and by protecting the soils from degradation. Thereby, on a 2-year basis, N2 fixation was evaluated in four oak woodlands under Mediterranean conditions using a split-plot design and three replicates. (15)N technique was used for determination of N2 fixation rate. Variations in environmental conditions (temperature, rainfall, radiation) by the cork tree canopy as well as the age of stands and pasture management can cause great differences in vegetation growth, legume N2 fixation, and soil rhizobial abundance. In the present study, non-legumes dominated the swards, in particular beneath the tree canopy, and legumes represented only 42% of total herbage. A 2-fold biomass reduction was observed in the oldest sown pasture in relation to the medium-age sward (6tDWha(-1)yr(-1)). Overall, competition of pasture growth for light was negligible, but soil rhizobial abundance and symbiotic N2 fixation capacity were highly favored by this environmental factor in the spring and outside the influence of tree canopy. Nitrogen derived from the atmosphere was moderate to high (54-72%) in unsown and sown swards. Inputs of fixed N2 increased from winter to spring due to more favorable climatic conditions (temperature and light intensity) for both rhizobia and vegetation growths. Assuming a constant fixation rate at each seasonal period, N2 fixation capacity increased from about 0.10kgNha(-1) per day in the autumn-winter period to 0.15kgNha(-1) per day in spring. Belowground plant material contributed to 11% of accumulated N in pasture legumes and was not affected by canopy. Size of soil fixing bacteria contributed little to explain pasture legumes N.
The following values have no corresponding Zotero field: publisher: Elsevier B.V. accession-num: 25460942
Keywords: Above and belowground organ; Agro forestry system; Cutting frequency; light; Quercus Suber L

Preliminary Investigation of LED Lighting as Growth Light for Seedlings from Different Tree Species in Growth Chambers - ASTOLFI, Stefania; MARIANELLO, Chiara; GREGO, Stefano; BELLAROSA, Rosanna (Notulae Botanicae Horti Agrobotanici Cluj-Napoca, 2012)
The influence of light quality on growth and metabolic activity during pre-cultivation (in miniplug containers) of beech (Fagus sylvatica L.), holm oak (Quercus ilex L.) and wild cherry (Prunus avium) plants was investigated. Seedlings were grown in a growth chamber for a month under light-emitting diode (LED) light or fluorescent light. The LED lamps (Valoya) used in this study emitted a continuous spectrum thanks to a mixture of blue, green, red and far-red LEDs. Our results showed that plant response to light quality seems to be related to the plant species. In particular, in beech seedlings fresh and dry weight, shoot height and leaf area were greatest when plants were cultured under LED light, and lowest under fluorescent lamps. Furthermore, we found that LED-induced reduction of chlorophyll contents in beech and holm oak leaves resulted in an increase of the carboxylase capacity of Rubisco in the same plant species suggesting an improvement of light-use-efficiency in these plants. These results indicate that LED light may be suitable for the culture of plants in tightly controlled environments. The comparison of malondialdehyde levels between LED and fluorescent grown plants strongly supports this idea.
Keywords: beech; glutamine synthetase; Holm oak; light; lipid peroxidation; Rubisco; wild cherry

Interspecific differences in sapling performance with respect to light and aridity gradients in Mediterranean pine–oak forests: implications for species coexistence - Zavala, MIGUEL a; Espelta, Josep M; Caspersen, John; Retana, Javier (Canadian Journal of Forest Research, 2011)
The relative abundance of two codominant Mediterranean tree species, shade-tolerant Quercus ilex L. and shade-intolerant Pinus halepensis Mill., is inversely correlated along aridity gradients, but this pattern is not explained by seedling responses to water or light availability, suggesting that subsequent life history stages may explain forest composition. To test this hypothesis, we calibrated statistical models of sapling growth and height–diameter allometry as functions of light availability and climatic variation as well as models of sapling mortality as a function of growth history. Contrary to the expectation of a sun–shade growth trade-off, P. halepensis grew faster than Q. ilex saplings at both low and high light levels. Low precipitation and aridity suppressed sapling growth rates, but no evidence of a shade–drought growth trade-off was found either. Pinus halepensis sapling mortality was strongly growth dependent, exhibiting high mortality rates at low growth, but the mortality of Q. ilex saplings was not. Height–diameter allometric variation was higher in low- than in high-light environments and was more pronounced with respect to changes in light than climatic water. Our results suggest that interspecific differences in sapling mortality and plasticity, rather than growth, may control species distributions at the mesic end of the aridity gradient.
doi: 10.1139/x11-050
Keywords: growth (voyant); light; Pinus halepensis; Quercus ilex; sapling mortality; Water availability

Root hydraulic conductance, gas exchange and leaf water potential in seedlings of Pistacia lentiscus L. and Quercus suber L. grown under different fertilization and light regimes - Hernández, E I; Vilagrosa, A; Luis, V C; Llorca, M; Chirino, E; Vallejo, V R (Environmental and Experimental Botany, 2009)
Differences in morphology, biomass allocations and physiological responses were investigated in seedlings of Mastic tree (Pistacia lentiscus L.) and Cork oak (Quercus suber L.) submitted to contrasting fertilization and light regimes during early growth. These species are two evergreen sclerophyllous Mediterranean species frequently used in Mediterranean reforestation programmes. Fertilization was the treatment that affected most of the morphological and physiological variables evaluated in P. lentiscus and Q. suber seedlings. Leaf area and speciﬁc leaf area (SLA) were affected by shading treatment in both species, showing higher values in seedlings grown under shade. P. lentiscus seedlings showed a high capacity to modify root morphological variables and root hydraulic conductance (KR) with the fertilization treatment. In contrast, Q. suber showed low to moderate root system changes with the treatments applied, although the fertilization level affected biomass allocation (i.e., root to shoot ratio) in both species. Under high water demand, P. lentiscus seedlings with high KR allowed transpiration (E) to increase without increasing the water potential gradient between soil and leaves. In Q. suber, high fertilization induced signiﬁcant increases in photosynthesis (A), as well as a tendency to increase E with signiﬁcantly lower leaf water potential ( L)
Keywords: Drought; fertilization; Gas exchange; light; Root hydraulic conductance

Oak seedling survival and growth along resource gradients in Mediterranean forests: implications for regeneration in current and future environmental scenarios - Gómez-Aparicio, L.; PÉREZ-RAMOS, I. M.; Mendoza, I.; Matías, L.; Quero, J. L.; Castro, J.; Zamora, R.; MARAÑON, T. (Oikos, 2008)
Understanding seedling performance across resource gradients is crucial for defining the regeneration niche of plant species under current environmental conditions and for predicting potential changes under a global change scenario. A 2-year field experiment was conducted to determine how seedling survival and growth of two evergreen and two deciduous Quercus species vary along gradients of light and soil properties in two Mediterranean forests with contrasting soils and climatic conditions. Half the seedlings were subjected to an irrigation treatment during the first year to quantify the effects on performance of an alteration in the summer drought intensity. Linear and non-linear models were parameterized and compared to identify major resources controlling seedling performance. We found both site-specific and general patterns of regeneration. Strong site-specificity was found in the identity of the best predictors of seedling survival: survival decreased linearly with increasing light (i.e. increasing desiccation risk) in the drier site, whereas it decreased logistically with increasing spring soil water content (i.e. increasing waterlogging risk) in the wetter site. We found strong empirical support for multiple resource limitation at the drier site, the response to light being modulated by the availability of soil resources (water and P). Evidence for regeneration niche partitioning among Quercus species was only found at the wetter site. However, at both sites Quercus species shared the same response to summer drought alleviation through water addition: increased first-year survival but not final survival (i.e. after two years). This suggests that extremely dry summers (i.e. the second summer in the experiment) can cancel out the positive effects of previous wetter summers. Therefore, an increase in the intensity and frequency of summer drought with climate change might cause a double negative impact on Quercus regeneration, due to a general reduction in survival probability and the annulment of the positive effects of (infrequent) ‘wet’ years. Overall, results presented in this study are a major step towards the development of a mechanistic model of Mediterranean forest dynamics that incorporates the idiosyncrasies and generalities of tree regeneration in these systems, and that allow simulation and prediction of the ecological consequences of resource level alterations due to global change.
Keywords: abiotic factors; growth (voyant); light; Mediterranean forests; Quercus; Regeneration; seedling survival; soil conditions; summer drought

Driving competitive and facilitative interactions in oak dehesas through management practices - Moreno Marcos, G; Obrador, J J; García, E; Cubera, E; Montero, M J; Pulido, F; Dupraz, C (Agroforestry Systems, 2007)
Dehesas are extant multi-purpose agroforestry systems that consist of a mosaic of widely-spaced scattered oaks (Quercus ilex L.) combined with crops, pasture or shrubs. We aimed to clarify the role of trees in dehesas of CW Spain focussed on the analysis of treeunderstorey interactions. Spatial variability of resources (light, soil moisture and fertility), microclimate, ﬁne roots of both herbaceous plants and trees and forage yield was measured. Additionally, we compared the nutritional and physiological status, growth and acorn production of oaks in cropped (fodder crop), grazed (native grasses) and encroached (woody understorey) dehesa plots. Signiﬁcant light interception by trees was limited to the close vicinity of the trees, with very low reduction away from them. Both microclimate and soil fertility improved signiﬁ- cantly in the trees vicinity, irrespective of soil management. Soil moisture varied very few with distance from the trees, as a result of the extended root system of oaks. Root systems of trees and herbs did not overlap to a great extent. Crop production was higher beneath trees than beyond the trees in unfertilised plots and foliar nutrient content of oaks did not increase signiﬁcantly with crop fertilisation, indicating that trees and crops hardly compete for nutrients. Moreover, trees beneﬁted from the crop or pasture management: trees featured a signiﬁcantly improved nutritional and physiological status, a faster growth and a higher fruit productivity than trees growing in encroached or forest plots.
Keywords: acorn production; forage yield; light; microclimate; root system; soil resources

Driving competitive and facilitative interactions in oak dehesas through management practices - Moreno Marcos, G.; Obrador, J. J.; García, E.; Cubera, E.; Montero, M. J.; Pulido, F.; Dupraz, C. (Agroforestry Systems, 2007)
Dehesas are extant multi-purpose agroforestry systems that consist of a mosaic of widely-spaced scattered oaks (Quercus ilex L.) combined with crops, pasture or shrubs. We aimed to clarify the role of trees in dehesas of CW Spain focussed on the analysis of treeunderstorey interactions. Spatial variability of resources (light, soil moisture and fertility), microclimate, ﬁne roots of both herbaceous plants and trees and forage yield was measured. Additionally, we compared the nutritional and physiological status, growth and acorn production of oaks in cropped (fodder crop), grazed (native grasses) and encroached (woody understorey) dehesa plots. Signiﬁcant light interception by trees was limited to the close vicinity of the trees, with very low reduction away from them. Both microclimate and soil fertility improved signiﬁ- cantly in the trees vicinity, irrespective of soil management. Soil moisture varied very few with distance from the trees, as a result of the extended root system of oaks. Root systems of trees and herbs did not overlap to a great extent. Crop production was higher beneath trees than beyond the trees in unfertilised plots and foliar nutrient content of oaks did not increase signiﬁcantly with crop fertilisation, indicating that trees and crops hardly compete for nutrients. Moreover, trees beneﬁted from the crop or pasture management: trees featured a signiﬁcantly improved nutritional and physiological status, a faster growth and a higher fruit productivity than trees growing in encroached or forest plots.
Keywords: acorn production; forage yield; light; microclimate; root system; soil resources

Sensitivity of volatile monoterpene emission to changes in canopy structure: a model-based exercise with a process-based emission model - Grote, Rüdiger (New Phytologist, 2007)
* • This paper investigates the dependence of monoterpene emissions at the canopy scale on total leaf area and leaf distribution. Simulations were carried out for a range of hypothetical but realistic forest canopies of the evergreen Quercus ilex (holm oak). * • Two emission models were applied that either did (SIM-BIM2) or did not (G93) account for cumulative responses to temperature and light. Both were embedded into a canopy model that considered spatial and temporal variations of foliage properties. This canopy model was coupled to a canopy climate model (CANOAK) to determine the micrometeorological conditions at the leaf scale. * • Structural properties considerably impacted monoterpene emission. The sensitivities to changes in total leaf area and to leaf area distribution were found to be of similar magnitude. The two different models performed similarly on a whole-year basis but showed clear differences during certain episodes. * • The analysis showed that structural indices have to be carefully evaluated for proper scaling of emission from leaves to canopy. Further research is encouraged on seasonal dynamics of emission potentials.
Keywords: Biological; biomass; foliage distribution; leaf area index; light; Models; monoterpene emission; Monoterpenes; Monoterpenes: metabolism; photosynthesis; Photosynthesis: radiation effects; Plant Leaves; Plant Leaves: metabolism; Plant Leaves: radiation effects; Quercus; Quercus ilex; Quercus: metabolism; Quercus: radiation effects; Scaling; stand density; Temperature; Time Factors; Volatilization

Dynamics of the enhanced emissions of monoterpenes and methyl salicylate, and decreased uptake of formaldehyde, by Quercus ilex leaves after application of jasmonic acid - Filella, Iolanda; Penuelas, Josep; Llusia, Joan (New Phytologist, 2006)
* • Jasmonic acid (JA) is a signalling compound with a key role in both stress and development in plants, and is reported to elicit the emission of volatile organic compounds (VOCs). Here we studied the dynamics of such emissions and the linkage with photosynthetic rates and stomatal conductance. * • We sprayed JA on leaves of the Mediterranean tree species Quercus ilex and measured the photosynthetic rates, stomatal conductances, and emissions and uptake of VOCs using proton transfer reaction mass spectrometry and gas chromatography after a dark–light transition. * • Jasmonic acid treatment delayed the induction of photosynthesis and stomatal conductance by approx. 20 min, and decreased them 24 h after spraying. Indications were found of both stomatal and nonstomatal limitations of photosynthesis. Monoterpene emissions were enhanced (20–30%) after JA spraying. Jasmonic acid also increased methyl salicylate (MeSa) emissions (more than twofold) 1 h after treatment, although after 24 h this effect had disappeared. Formaldehyde foliar uptake decreased significantly 24 h after JA treatment. * • Both biotic and abiotic stresses can thus affect plant VOC emissions through their strong impact on JA levels. Jasmonic acid-mediated increases in monoterpene and MeSa emissions might have a protective role when confronting biotic and abiotic stresses.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd accession-num: 16390425
Keywords: Carbon dioxide; Carbon Dioxide: metabolism; Cyclopentanes; Cyclopentanes: pharmacology; Dehydration; Formaldehyde; Formaldehyde: metabolism; jasmonic acid (JA); light; methyl salicylate; Monoterpenes; Monoterpenes: metabolism; net photosynthetic rates; Oxylipins; photosynthesis; Plant Leaves; Plant Leaves: drug effects; Plant Leaves: metabolism; Quercus; Quercus ilex (holm oak); Quercus: drug effects; Quercus: metabolism; Salicylates; Salicylates: metabolism; Stomatal conductance; Temperature; VOC (volatile organic compound)

Dynamics of the enhanced emissions of monoterpenes and methyl salicylate, and decreased uptake of formaldehyde, by Quercus ilex leaves after application of jasmonic acid - Filella, Iolanda; Penuelas, Josep; Llusia, Joan (New Phytologist, 2006)
* • Jasmonic acid (JA) is a signalling compound with a key role in both stress and development in plants, and is reported to elicit the emission of volatile organic compounds (VOCs). Here we studied the dynamics of such emissions and the linkage with photosynthetic rates and stomatal conductance. * • We sprayed JA on leaves of the Mediterranean tree species Quercus ilex and measured the photosynthetic rates, stomatal conductances, and emissions and uptake of VOCs using proton transfer reaction mass spectrometry and gas chromatography after a dark–light transition. * • Jasmonic acid treatment delayed the induction of photosynthesis and stomatal conductance by approx. 20 min, and decreased them 24 h after spraying. Indications were found of both stomatal and nonstomatal limitations of photosynthesis. Monoterpene emissions were enhanced (20–30%) after JA spraying. Jasmonic acid also increased methyl salicylate (MeSa) emissions (more than twofold) 1 h after treatment, although after 24 h this effect had disappeared. Formaldehyde foliar uptake decreased significantly 24 h after JA treatment. * • Both biotic and abiotic stresses can thus affect plant VOC emissions through their strong impact on JA levels. Jasmonic acid-mediated increases in monoterpene and MeSa emissions might have a protective role when confronting biotic and abiotic stresses.
Keywords: Carbon dioxide; Carbon Dioxide: metabolism; Cyclopentanes; Cyclopentanes: pharmacology; Dehydration; Formaldehyde; Formaldehyde: metabolism; jasmonic acid (JA); light; methyl salicylate; Monoterpenes; Monoterpenes: metabolism; net photosynthetic rates; Oxylipins; photosynthesis; Plant Leaves; Plant Leaves: drug effects; Plant Leaves: metabolism; Quercus; Quercus ilex (holm oak); Quercus: drug effects; Quercus: metabolism; Salicylates; Salicylates: metabolism; Stomatal conductance; Temperature; VOC (volatile organic compound)

Effects of the interaction between drought and shade on water relations, gas exchange and morphological traits in cork oak (Quercus suber L.) seedlings - Aranda, I.; Castro, L.; Pardos, M.; Gil, L.; Pardos, J. a (Forest Ecology and Management, 2005)
The combined effect of drought and light on different physiological and biochemical traits was assessed in cork oak (Quercus suber L.) seedlings grown under two levels of light availability and submitted to a long-standing drought. Watering was withdrawn after germination and seedlings were allowed to dry to a water content of ca. 50% of ﬁeld capacity. At this point, water-stressed seedlings were grown under moderate drought and two light regimes: high light (HL—50%) and low light (LL— 2%). Soil water in control plants was kept close to ﬁeld capacity (90–100%) for both light environments. Water-relations parameters derived from P–V curves, gas exchange and water status at predawn (Cpd ) were evaluated at twice during the experiment. Nitrogen and chlorophyll contents were determined in the same leaves used for the gas exchange measurements. In addition, maximum rate of carboxylation (Vcmax) and electronic transport (Jmax) were derived from A–Ci curves in well-watered seedlings. The variation on moisture availability during the experiment was the same under both light environments. In control plants, Cpd was over 0.3 MPa at the two harvests, while stressed seedlings decreased to 0.9 MPa, with no differences between light treatments. Water stress decreased osmotic potentials at full (Cp100 ) and zero turgor (Cp0 ). The regressions between both potentials and Cpd showed a higher intercept in shade grown seedlings. This fact will point out the higher osmoregulation capacity in sun seedlings whatever water availability. Nitrogen investment on a per leaf mass (Nmass ), chlorophyll content (Chlmass ) and SLA tended to show a typical pattern of sun-shade acclimation. Thus, the three parameters increased with shade. Only for Nmass there was a signiﬁcant effect of watering, since water stress increased Nmass . LL plants showed a lower photosynthetic capacity in terms of maximum net photosynthesis at saturating light (Amax), which was related to a decrease in Vcmax and Jmax . Both parameters varied with speciﬁc leaf area (SLA) in a similar way. The low-light environment brought about a higher nitrogen investment in chlorophyll, while under high-light environment the investment was higher in carboxylation (Vcmax) and electronic transport ( Fmax). Stomatal conductance to water vapour (gwv ) and Amax were lower in low-light seedlings independently of watering. In addition, there was a trend to keep higher intrinsic water use efﬁciency (IWUE) under high light environment. The increase of IWUE under water stress was higher in HL seedlings. This was as consequence of the steeper decline in gwv as Cpd decreased. The decrease of Amax with Cpd occurred in a similar way in LL and HL seedlings. Thus, the HL seedlings tended to sustain a higher ability to increase IWUE than LL seedlings when they were submitted to the same water stress.
Keywords: Cork oak; Drought; light; osmotic adjustment; photosynthesis; water use efficiency

Penetration of UV-A, UV-B and blue light through the leaf trichome layers of two xeromorphic plants, olive and oak, measured by optical fibre microprobes - Karabourniotis, George; Bornman, Janet F. (Physiologia Plantarum, 1999)
Quartz fibre-optic microprobes were used to monitor the light microenvironment beneath trichome layers of the xeromorphic leaves of two Mediterranean evergreen sclerophylls, Olea europaea and Quercus ilex. Young developing leaves of both plants were densely pubescent on both surfaces of the lamina, whereas the mature leaves were pubescent only on the abaxial side. Trichome layers of young as well as of mature leaves of both plants attenuated almost all incident ultraviolet (UV)-B (310 nm) and UV-A (360 nm) radiation and a considerable portion of blue light (430 nm). Abaxial trichome layers of young leaves were more effective in screening out the incident radiation compared to the adaxial ones of the same leaves and also compared to the abaxial layer of the mature leaves. The abaxial epidermis of dehaired mature leaves of O. europaea was ineffective in absorbing most of the incident UV-B and UV-A radiation. UV and visible spectra beneath trichome layers of O. europaea in mature leaves confirmed that the light microenvironment on the epidermis was deprived in the UV-B, UV-A and partly in the blue spectral regions. It is proposed that the occurrence of a dense trichome layer, especially in young leaves, may play a protective role against not only UV-B radiation damage, but also against high visible irradiance. This function is performed irrespective of the differing anatomy of individual hairs of both plants. The protection provided by the trichomes could afford advantages under stress conditions, especially during leaf development.
The following values have no corresponding Zotero field: publisher: Munksgaard International Publishers
Keywords: Abaxial; Adaxial (voyant); leaves; light; trichome layers

Penetration of UV-A, UV-B and blue light through the leaf trichome layers of two xeromorphic plants, olive and oak, measured by optical fibre microprobes - Karabourniotis, George; Bornman, Janet F (Physiologia Plantarum, 1999)
Quartz fibre-optic microprobes were used to monitor the light microenvironment beneath trichome layers of the xeromorphic leaves of two Mediterranean evergreen sclerophylls, Olea europaea and Quercus ilex. Young developing leaves of both plants were densely pubescent on both surfaces of the lamina, whereas the mature leaves were pubescent only on the abaxial side. Trichome layers of young as well as of mature leaves of both plants attenuated almost all incident ultraviolet (UV)-B (310 nm) and UV-A (360 nm) radiation and a considerable portion of blue light (430 nm). Abaxial trichome layers of young leaves were more effective in screening out the incident radiation compared to the adaxial ones of the same leaves and also compared to the abaxial layer of the mature leaves. The abaxial epidermis of dehaired mature leaves of O. europaea was ineffective in absorbing most of the incident UV-B and UV-A radiation. UV and visible spectra beneath trichome layers of O. europaea in mature leaves confirmed that the light microenvironment on the epidermis was deprived in the UV-B, UV-A and partly in the blue spectral regions. It is proposed that the occurrence of a dense trichome layer, especially in young leaves, may play a protective role against not only UV-B radiation damage, but also against high visible irradiance. This function is performed irrespective of the differing anatomy of individual hairs of both plants. The protection provided by the trichomes could afford advantages under stress conditions, especially during leaf development.
Keywords: Abaxial; Adaxial (voyant); leaves; light; trichome layers

EMISSION OF SHORT CHAINED ORGANIC ACIDS , ALDEHYDES AND MONOTERPENES FROM QUERCUS ILEX L . AND PINUS PINEA L . IN RELATION TO PHYSIOLOGICAL ACTIVITIES , CARBON BUDGET AND EMISSION ALGORITHMS - Kesselmeier, J; Bode, K; Hofmann, U; Mtjller, H; Schafer, L; Wolf, A; Ciccioli, P; Cecinato, A; Frattoni, M; Foster, P; Dutaur, L; Torreq, L (Atmospheric Environment, 1997)
We report on the emission of monoterpenes, short-chained organic acids and aldehydes from Mediterranean oak (Quercus ilex L.) and pine (Pinus pinea L.). All studies were done with dynamic cuvettes enclosing intact branches at the top of the canopy flushed with ambient air. Daily trends are compared with the photosynthetic active radiation (PAR), leaf temperature and the physiological activities of the enclosed branches, i.e. assimilation and transpiration, with special attention on the carbon budget. Oak emits monoterpenes in high amounts, up to 2% of the assimilated carbon. As compared with monoterpenes, short-chained organic acids and aldehydes are of minor importance for oak. However, on a leaf dry-weight basis equal amounts of acids and aldehydes are released from oak and pine. As pine emitted only low amounts of terpenes (below 0.2% of the assimilated carbon) the release of terpenes and oxygenated compounds is of equal importance for this species. A comparison of a modelled light and temperature driven emission with the observed volatile organic compounds (VOC) emissions showed good agreement for monoterpenes as well as for organic acids emitted in the case of oak. For pine only the release of acids showed an adequate relation to the algorithm data, whereas the terpene emissions seemed to be dominated by temperature effects
Keywords: aldehydes; carbon budget; coniferous; deciduous; light; Monoterpenes; oak; organic acids; pine; Pinus pinea L; Plant physiology; Quercus ilex L; Temperature; Volatile Organic Compounds

Supervivencia y crecimiento de plántulas de encina en función de la intensidad de luz y la disponibilidad de agua - J.Ma, ESPELTA; RETANA, J; Riba, M (II Congreso Forestal Español, 1997)
The response of holm oak seedlings under a gradient of light and water av ail abilit y is analyzed. Seedling survival under all water levels decreased with increasing light. Conceming seedling morphology, both light and water availability changed biomass allocation to roots, stems and leaves, being light the most important source of variation
Keywords: Holm oak; light; Regeneration; Seedling; water

EMISSION OF MONOTERPENES AND ISOPRENE FROM A MEDITERRANEAN OAK SPECIES QUERCUS ILEX L. MEASURED WITHIN THE BEMA (BIOGENIC EMISSIONS IN THE MEDITERRANEAN AREA) PROJECT EMISSIONS IN THE M E D I T E - Kesselmeier, J; Fer, L S C H; Ciccioli, P; Brancaleoni, E; Cecinato, A; Frattoni, M; Foster, I P; Jacob, V; Denis, J; Fugit, J L; Dutaur, L; Torres, L; et al. (Atmospheric Environment, 1996)
We report on some results of our studies of monoterpene and isoprene emissions and the physiological activities of an oak species (Quercus ilex L.) under the Mediterranean climatic conditions found at Castel Porziano (Rome) in June 1993. The oak species Quercus ilex L. was found to emit mainly monoterpenes in high amounts. Isoprene emissions were negligible. Diel cycles of monoterpene emissions showed correlation with light and the diel behaviour of photosynthetic CO2 assimilation, transpiration and stomatal corductance. Temperature dependence seemed to be of minor importance.
Keywords: Biogenic emission; isoprene; light; Monoterpenes; non-methane hydrocarbons; oak; Plant physiology; VOC